Islamic Hedging: Concept Analysis and Implementation in the Islamic Financial System - Muhammad Mashduqi; Khusnudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Islamic hedging is one of the instruments in financial management used to reduce risks associated with price and currency movements. Muslim economists, in offering mainstream hedging reform by removing the elements of shari'ah violation and incorporating shari'ah contracts into it. However, have the elements that cause hedging to be prohibited been thoroughly eliminated. This noble cause of Islamic hedging has been misunderstood for profit only. Therefore, the concept of Islamic hedging needs further discussion due to various interpretations of the meaning of Islamic hedging. To obtain answers to this research, the author uses qualitative research with the type of inferential library research. The results of this study, in simple terms, can be concluded that the application of Islamic hedging that has been implemented in the Islamic financial system is in accordance with the provisions, both the provisions of the Fatwa DSN-MUI, PBI and DPS.